Pendampingan Pembuatan dan Pengelolaan Sistem Informasi Desa dan Covid-19 - Riza Ibnu Adam; Apriade Voutama; Farradina Choria Suci; Vita Efelina; Muhammad Jodi Ramadhan Sumantri (Communautaire: Journal of Community Service, 2023)
Pasirjengkol Village is a village that is domiciled in Majalaya District, Karawang Regency. So far, they have experienced difficulties with information systems in the form of websites related to the Covid-19 pandemic, so they have never created or managed information systems for the public. The problems encountered are due to the limited ability of village government officials and employees in creating and managing information systems, as well as limited operational support facilities and infrastructure including computers. There are community service activities through mentoring activities, creation and management of a Covid-19 information system that is capable of assisting the routine operations of the Covid-19 task force in Pasirjengkol Village and compiling a guidebook for using the website-based Covid-19 information system in Pasirjengkol Village.